Comparative study of root characteristics revealed distinctive responses between Moroberekan and MR297 rice varieties subjected to drought stress - MOHD FAUZIHAN KARIM; NUR HAMIZATUN NABILAH TAJUDIN; SITI AISAH SALMIN; NUR FARAH SUHADA MOHD ROSELY; NUR NAZIFAH SAIMI; CHE NURUL AINI CHE AMRI (Nusantara Bioscience, 2024)
Abstract. Karim MF, Tajudin NHN, Salmin SA, Rosely NFSM, Saimi NN, Amri CNAC. 2024. Comparative study of root characteristics revealed distinctive responses between Moroberekan and MR297 rice varieties subjected to drought stress. Nusantara Bioscience 16: 29-36. In light of the growing concern over climate change, it is crucial to comprehend how the rice plant, Oryza sativa L., responds to various environmental stress, particularly prolonged drought. This study investigated the morphological and anatomical characteristics of the roots of rice plants following a continuous drought on two selected varieties: MR297, known to produce a high yield but is highly sensitive to low water potential, and Moroberekan, known to be drought tolerant. The drought treatment was initiated on day 24 after sowing and continued for seven days or until any plant exhibited curled leaves. There was no significant difference in root length between the two varieties, but MR297 had substantially lower fresh and root dry weights (32.5% and 40%, respectively) than Moroberekan under drought stress. Drought also significantly affected root electrolyte leakage and MDA content, especially in MR297 compared to Moroberekan. Meanwhile, root anatomy studies have revealed differences between the control and drought treatments. While the root diameter of the control plants was greater, their aerenchyma cells were less developed than those of the drought-induced plants, which had a higher ratio of aerenchyma cells per sectioned area. The number of metaxylem was reduced by drought, but the effect was more pronounced in MR297 than in Moroberekan. This study provides evidence of the impact of drought on both Moroberekan and MR297, as observed through their root morpho-physiology and anatomical structure.